Lower mitochondrial DNA content but not increased mutagenesis associates with decreased base excision repair activity in brains of AD subjects - Soltys, Daniela T.; Pereira, Carolina P.M.; Rowies, Fernanda T.; Farfel, José M.; Grinberg, Lea T.; Suemoto, Claudia K.; Leite, Renata E.P.; Rodriguez, Roberta D.; Ericson, Nolan G.; Bielas, Jason H.; Souza-Pinto, Nadja C. (Neurobiology of aging, 2019)
Accumulation of oxidative mitochondrial DNA (mtDNA) damage and impaired base excision repair (BER) in brains have been associated with Alzheimer's disease (AD). However, it is still not clear how these affect mtDNA stability, as reported levels of mtDNA mutations in AD are conflicting. Thus, we investigated whether alterations in BER correlate with mtDNA instability in AD using postmortem brain samples from cognitively normal AD subjects and individuals who show neuropathological features of AD, but remained cognitively normal (high-pathology control). To date, no data on DNA repair and mtDNA stability are available for these individuals. BER activities, mtDNA mutations, and mtDNA copy number were measured in the nuclear and mitochondrial extracts. Significantly lower uracil DNA glycosylase activity was detected in nuclear and mitochondrial extracts from AD subjects, while apurinic/apyrimidinic endonuclease activity was similar in all groups. Although mtDNA mutation frequency was similar in all groups, mtDNA copy number was significantly decreased in the temporal cortex of AD brains but not of high-pathology control subjects. Our results show that lower mitochondrial uracil DNA glycosylase activity does not result in increased mutagenesis, but rather in depletion of mtDNA in early-affected brain regions during AD development.